Processing of TiC-CNT hybrid composite coating on low alloy steel using TIG Torch technique - Maleque, Md. Abdul; Bello, K. A; Md Idriss, Ahmed Nazrin; Mirdha, S. (Trans Tech Publications Ltd., Switzerland, 2013)
In the present study, a surface layer of TiC-CNT hybrid compositecoating has been developed on low alloy steel (LAS) by using powder preplacement and tungsten inert gas (TIG) torch melting techniques.The weighed powder mixture with the content of 1.0 mg per millimeter square area and containing TiC- 4wt. % CNT particles was preplaced on LAS surfaces using a suitable binder and then melted under the TIG arc with an operating current of 100 A and energy input of 1440 J/mm. The microstructural and microhardness characteristics of the processed composites coating were analyzed using SEM, EDXand Vickers microhardness testers. Under the melting condition used in this investigation, the arc completely dissolved the composite powder mixture that resolidifiedinto a melt track with radial marks and smooth surfaces. Themelt cross sections were hemispherical in shape and produced 1 mm deep hard coating layer which were free from porosity and cracks. SEM micrographs TiC-CNT hybrid coated surface glazed at 100A consists of fineprecipitated TiC in form globular and cubic dendrites and this is the reason for hardness increment to an average of three times greater than that of substrate value. The result obtained indicated that TIG arc melting process is applicable to generate resolidified layer of precipitated TiC microstructure with uniformly distribution in the coating region.